Proceedings of the Second International Conference on Internet-of-Things Design and Implementation 2017
DOI: 10.1145/3054977.3054979
|View full text |Cite
|
Sign up to set email alerts
|

SafeWatch

Abstract: Driving with distraction or losing alertness increases the risk of the traffic accident. The emerging Internet of Things (IoT) systems for smart driving hold the promise of significantly reducing road accidents. In particular, detecting the unsafe hand motions and warning the driver using smart sensors can improve the driver's self-alertness and the driving skill. However, due to the impact of the vehicle's movement and the significant variation across different driving environments, detecting the position of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In terms of driving applications, there are ear-worn head nodding detectors [4]. Particularly, previous work [7] used two smartwatches and a smartphone to monitor manual distractions. Compared to such multi-wearable designs, our system has three unique advantages: first, the magnetic tags are low cost and they don't require battery recharge.…”
Section: Discussion 81 Multi-wearable Designs and Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of driving applications, there are ear-worn head nodding detectors [4]. Particularly, previous work [7] used two smartwatches and a smartphone to monitor manual distractions. Compared to such multi-wearable designs, our system has three unique advantages: first, the magnetic tags are low cost and they don't require battery recharge.…”
Section: Discussion 81 Multi-wearable Designs and Applicationsmentioning
confidence: 99%
“…Wearable technologies have been used to monitor driving activity. For example, previous research used inertial measurement units (IMUs), commonly found on smartwatches, to detect erratic steering wheel movements [6] and manual distractions [7], but these solutions are limited to the detection of the hands where smartwatches are worn. Therefore, the development of reliable, robust, and low-cost technologies to monitor various driver activities is desirable.…”
Section: Introductionmentioning
confidence: 99%
“…Because the driver's driving posture when holding the steering wheel is similar to the posture of other events, such as the user holding a book on the table with both hands or holding the left and right sides of an iPad, only д x,watch is used to detect the forearm gesture of the driver's hand holding the steering wheel is not enough. So we introduce the vibration signal in the vertical direction, which is one feature that detects whether the driver's hand is on the steering wheel in [5]. When the engine of the vehicle is started, continuous vibration in the vertical direction is generated and radiated into the cockpit.…”
Section: Driving Posture Detection Algorithmmentioning
confidence: 99%
“…In the driving environment, the detection of a relative movement between the vehicle and the driver's hand can be used to indicate that the driver's hand may be operating the steering wheel. We leverage the work from Bi et al [5] to detect if the driver's hand is moving by comparing the acceleration of the smart watch ( a w ) and the acceleration of the smart phone (| a p |) [20]. Since the coordinates of the smart phone and the smart watch are not aligned, the components of the acceleration of the two devices in various directions cannot be directly compared.…”
Section: Steering Wheel Movementmentioning
confidence: 99%